2017
DOI: 10.1186/s13010-017-0046-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, legal and societal considerations on Zika virus epidemics complications in scaling-up prevention and control strategies

Abstract: Much of the fear and uncertainty around Zika epidemics stem from potential association between Zika virus (ZIKV) complications on infected pregnant women and risk of their babies being born with microcephaly and other neurological abnormalities. However, much remains unknown about its mode of transmission, diagnosis and long-term pathogenesis. Worries of these unknowns necessitate the need for effective and efficient psychosocial programs and medical-legal strategies to alleviate and mitigate ZIKV related burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…The public health response to Zika should consider how women's organizations interact with the overall society, how they support each other, and whether networks between them do exist. The ability of local communities to mobilize and collaborate for action influences the success of strategies to control infectious disease [21]. Community engagement could be an essential tool to minimize suffering, increase emotional and mental health and support among ZIKV patients and families with affected children.…”
mentioning
confidence: 99%
“…The public health response to Zika should consider how women's organizations interact with the overall society, how they support each other, and whether networks between them do exist. The ability of local communities to mobilize and collaborate for action influences the success of strategies to control infectious disease [21]. Community engagement could be an essential tool to minimize suffering, increase emotional and mental health and support among ZIKV patients and families with affected children.…”
mentioning
confidence: 99%
“…Community engagement -i.e., the sharing of information, trust, and responsibility between health authorities and affected communities (Schoch-Spana et al, 2007) -was a recurrent theme in the ethics analyses published during the Zika virus outbreak (Nuffield Council on Bioethics, 2016;PAHO, 2016;Tambo et al, 2017). The Pan American Health Organization and Nuffield Council on Bioethics, for instance, advised providing clear, timely, and culturally-aware public information about the health effects including congenital Zika syndrome, local incidence and prevalence, personal protective actions (e.g., repellent use), and public health interventions (e.g., surveillance) (Nuffield Council on Bioethics, 2016;PAHO, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the public health ethics of Zika virus vector control demonstrated that community engagement is vital (Jamrozik et al, 2018;Nuffield Council on Bioethics, 2016;Tambo et al, 2017;WHO, 2017). Interventions seen as out-of-sync with local values could foster community resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public health response to Zika should consider how women's organizations interact with the overall society, how they support each other, and whether networks between them do exist. The ability of local communities to mobilize and collaborate for action influences the success of strategies to control infectious disease [22].…”
Section: Introductionmentioning
confidence: 99%